TINJAUAN SOSIOLOGI KELUARGA TERHADAP POLA KETAHANAN ISTRI DALAM MENGATASI PROBLEMATIKA KELUARGA MUSLIM PADA MASA PANDEMI DI DESA DAREK KECAMATAN PRAYA BARAT DAYA - Intan Septiana; Tuti Harwati; Imron Hadi (Al-IHKAM: Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2022)
This research was carried out starting by looking at the social reality of the Darek village in the midst of the Covid-19 pandemic, where domestic violence is frequent and does not seldom lead to divorce. The purpose of this research is to find out what problems wives use in resolving problems that are faced during the pandemic in Darek village. The study uses qualitative research methods, so researchers go to the environment to obtain valid data. Research conducted by researchers has found results that there are facing the family during the Covid-19 in Darek village, besides that efforts to maintain family integrity were also continuously carried out, more specifically by the wife in this study. Based on the results of the study, the researchers concluded that the occurrence of this pandemic would cause a shock culture in Darek village. These difficult situations often create conflict in the household and make the wife a victim, but behind the adversity, there are also many wives who are able to maintain the integrity of their families, even the wife’s creative strategies in reducing family conflicts have been successful in maintaining the integrity of their families during the pandemic until now.